Students' Problems in Online Learning: What Happened to the Students in English Class During Pandemic Covid-19? - Tira Nur Fitria (Journal of English Language Learning, 2023)
This research describes problems faced by students of ITB AAS Indonesia in the implementation of online learning during the pandemic Covid-19 in the academic year 2020/2021. This research uses qualitative research. The analysis results show that during online learning in English class, students’ problems are: 1) concentration during learning. 2) feeling bored and lazy during learning. 3) slow or unstable internet network. 4) expensive internet quota prices. 5) technical problems with learning devices such as computers, laptops, or cellphones. 6) adaptation to digital technology such as video-conferencing applications. 7) the circumstances that are not conducive at home. 8 communicating and interacting with the lecturer and classmates. 9) managing work and study time. 10) accessing institutional e-learning or other learning applications. 11) understanding English learning materials. 12) doing the English assignments and homework given by the lecturer. 14) the total number of English assignments is too much. 13) having limited time for doing English assignments and homework. 14) the lecture schedule is not adjusted to the proper lecture schedule. 15) lecturers have a limited learning method during teaching online. 16) feeling worried and anxious about the English midterm exam and the final exam including the question type, number, or level of difficulty of questions and the implementation of online exams during online learning. 17) feeling worries and anxiety about the English final grade or score that will be obtained at the end of the semester. As teachers or lecturers, we have to find various solutions to overcome the problems.